Peran Moderasi Pengetahuan Produk Dan Keinovativan Pelaku Bisnis Dalam Pengaruh Dimensi Pertimbangan Pada Niat Menjadi Nasabah Bank Syariah, Studi Pada Pengusaha Kecil Dan Menengah Di Surakarta - Nurtantiono, Andri (STIE Surakarta, 2012)
This study objective to analyze the influence of Attitude, Subjective Norm and Perceived Behavior Control The Intention Of Becoming Customer moderated by Knowledge Products And Innovation. The problems posed and formulated is: Do Attitudes, Subjective Norms and Control of the perceived behavior of the business together and the partial effect on the intention to customers of Islamic banks in the city of Surakarta, whether the moderating effect of product Knowledge Attitude, Subjective Norms and Perceived Behavior Control of Intention to be a customer, and whether the level of business innovation moderate the effect of Attitude, Subjective Norm and Perceived Behavioral Control of Intention to customers.Data analysis was performed with the Multiple Regression and Test Interactions to analyze the influence of moderating variables and the level of Product Knowledge Innovation, showed that (1) Attitude, Subjective Norms and Perceived Behavioral Control jointly affect a customers intent, (2) Partially, attitude does not significantly influence the intention to customers of Islamic banks in the city of Surakarta. While variable Subjective Norms and Behavioral Control of perceived intention to significantly affect customers, (3) Knowledge of good products do not moderate the influence of attitude on intention as a customer, Subjective Norms intentions as a customer and. Perceived behavior control to intention as a customer, (4) Rate of Innovation moderating effect only on Subjective Norms and Perceived Behavioral Control of intention to become a customer.